The Research Council of Norway: Implementing a new model for financing gold-OA - Løvhaug, Johannes W. (Septentrio Conference Series, 2014)
>> See video of presentation (27 min.) The Research Council of Norway has recently revised its policy on Open Access and has decided to follow up the policy by implementing a new model for financing APCs. The new financing scheme, called STIM-OA, is directed towards the already existing publication funds at the Norwegian research institutions. The funds will from 2015 be able to apply STIM-OA for up to 50 % of their OA-expenses the previous year. STIM-OA will make a substantial contribution to the publication funds. Furthermore the scheme aims at structuring the financial and administrative handling of APCs at the institutional level. The goal of STIM-OA is to contribute financially in a transitional period, but in the future the Research Council expects to finance APCs as normal indirect cost for the research institutions, the same way as subscription fees are handled today.